Biological and Molecular Effects of Trypanosoma cruzi Residence in a LAMP-Deficient Intracellular Environment - Oliveira, Anny Carolline Silva; Rezende, Luisa; Gorshkov, Vladimir; Melo-Braga, Marcella Nunes; Verano-Braga, Thiago; Fernandes-Braga, Weslley; Guadalupe, Jorge Luís de Melo; de Menezes, Gustavo Batista; Kjeldsen, Frank; de Andrade, Hélida Monteiro; Andrade, Luciana de Oliveira (Frontiers in Cellular and Infection Microbiology, 2022)
Trypanosoma cruzi invades non-professional phagocytic cells by subverting their membrane repair process, which is dependent on membrane injury and cell signaling, intracellular calcium increase, and lysosome recruitment. Cells lacking lysosome-associated membrane proteins 1 and 2 (LAMP1 and LAMP2) are less permissive to parasite invasion but more prone to parasite intracellular multiplication. Several passages through a different intracellular environment can significantly change T. cruzi’s gene expression profile. Here, we evaluated whether one single passage through LAMP-deficient (KO) or wild-type (WT) fibroblasts, thus different intracellular environments, could influence T. cruzi Y strain trypomastigotes’ ability to invade L6 myoblasts and WT fibroblasts host cells. Parasites released from LAMP2 KO cells (TcY-L2−/−) showed higher invasion, calcium signaling, and membrane injury rates, for the assays in L6 myoblasts, when compared to those released from WT (TcY-WT) or LAMP1/2 KO cells (TcY-L1/2−/−). On the other hand, TcY-L1/2−/− showed higher invasion, calcium signaling, and cell membrane injury rates, for the assays in WT fibroblasts, compared to TcY-WT and TcY-L1/2−/−. Albeit TcY-WT presented an intermediary invasion and calcium signaling rates, compared to the others, in WT fibroblasts, they induced lower levels of injury, which reinforces that signals mediated by surface membrane protein interactions also have a significant contribution to trigger host cell calcium signals. These results clearly show that parasites released from WT or LAMP KO cells are distinct from each other. Additionally, these parasites’ ability to invade the cell may be distinct depending on which cell type they interact with. Since these alterations most likely would reflect differences among parasite surface molecules, we also evaluated their proteome. We identified few protein complexes, membrane, and secreted proteins regulated in our dataset. Among those are some members of MASP, mucins, trans-sialidases, and gp63 proteins family, which are known to play an important role during parasite infection and could correlate to TcY-WT, TcY-L1/2−/−, and TcY-L2−/− biological behavior.